1987
DOI: 10.1002/jsfa.2740410205
|View full text |Cite
|
Sign up to set email alerts
|

A nutritional assessment of African yam bean Sphenostylis stenocarpa (Hochst ex A. Rich) Harms, and bambara groundnut Voandzeia subterranea L.

Abstract: Two grain legumes Sphenostylis stenocarpa (Hochst ex A . Rich) Harms. and Voandzeia subterranea L. commonly grown in the tropics for human consumption, were evaluated nutritionally using broiler chick assays. Metabolisable energy content was high in both pulses, but true protein digestibility was low in S . stenocarpa (62.9%) and moderate in V . subterranea (77.0%). Both mineral content and availability were moderate. Amino acid content was similar to that of other pukes, cystine and methionine being low. Amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
5

Year Published

1992
1992
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 9 publications
8
38
5
Order By: Relevance
“…The CP and crude fi bre content of Bambara groundnut determined in this study were about 22 and 5.2%, respectively, similar to those reported from other studies (Nwokolo, 1987;Ologhobo, 1992). However, the content of ether extract (7.5%) in this study was much higher than the 2.85 % reported by Nwokolo (1987).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The CP and crude fi bre content of Bambara groundnut determined in this study were about 22 and 5.2%, respectively, similar to those reported from other studies (Nwokolo, 1987;Ologhobo, 1992). However, the content of ether extract (7.5%) in this study was much higher than the 2.85 % reported by Nwokolo (1987).…”
Section: Discussionsupporting
confidence: 88%
“…However, the content of ether extract (7.5%) in this study was much higher than the 2.85 % reported by Nwokolo (1987). The similarity in the nutrients content from this study to those of Nwokolo (1987) and Ologhobo (1992) could be due to the fact that the nuts all originating from the same geographical region (West Africa). The differences in the nutrient content found in this study to those reported by the authors in the introduction could be to a large extent due to the geographical origin and also the cultivar used.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations